Cost Effectiveness Analysis Trastuzumab Deruxtecan Versus Trastuzumab Emtansine Pada Pasien Kanker Payudara Metastatik Her2-Positif: Systematic Review - Juan Balapradhana Santoso (CV. AFDIFAL MAJU BERKAH, 2026)
HER2-positive breast cancer is one of the subtypes of breast cancer with a poor prognosis and a strong need for effective targeted therapies. Trastuzumab deruxtecan (T-DXd) and trastuzumab emtansine (T-DM1) are two antibody-drug conjugates (ADCs) used as second-line treatments for patients with this condition. To evaluate the cost-effectiveness between T-DXd and T- DM1 through a systematic review of relevant literature. Literature search was conducted using Scopus, PubMed, Science Direct, and Google Scholar databases with the keywords “cost effectiveness analysis” AND “metastatic breast cancer” OR “HER2-positive breast cancer” AND “trastuzumab deruxtecan” AND “trastuzumab emtansine”. A total of 521 articles were identified, but only 4 met the inclusion criteria. T-DXd was considered more cost-effective in high- income countries such as the United States (ICER as low as 13,342/QALY) and Finland (ICER approximately €55,360/QALY), but not in China, where the ICER reached 186,017/QALY,